2018
DOI: 10.1242/bio.035923
|View full text |Cite
|
Sign up to set email alerts
|

Viability of dietary substitution of live microalgae with dry Ulva rigida in broodstock conditioning of Pacific oyster (Crassostrea gigas)

Abstract: The current study evaluated the microalgae replacement by dry macroalgae (Ulva rigida) in the reproductive success and biochemical composition of the Pacific oyster (Crassostrea gigas) during broodstock conditioning. Five nutritional regimes were tested: 100% macroalgae (diet 1), 50% macroalgae+50% microalgae (diet 2), 25% macroalgae+75% microalgae (diet 3) and 100% microalgae (diet 4). An unfed group was used as a negative control. The microalgae blend was composed of 33% Isochrysis galbana and 67% diatoms (7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 67 publications
0
4
0
Order By: Relevance
“…A low metabolic rate is sometimes an explanation for low accumulation rates (Pavlov et al, ). Indeed, the viability results associated with this study on broodstock conditioning of C. gigas (Rato et al, ) have shown that SW100 oysters exhibited a higher mortality when compared to SW0 and the remaining feeds, being unable to meet the demands for maintenance—a lower standard metabolic rate was measured in the SW100 oysters than in SW0 oysters (Ozório et al, ). Hence, a more satisfactory explanatory hypothesis would be differences in the growth rates between the various SW groups.…”
Section: Resultsmentioning
confidence: 75%
“…A low metabolic rate is sometimes an explanation for low accumulation rates (Pavlov et al, ). Indeed, the viability results associated with this study on broodstock conditioning of C. gigas (Rato et al, ) have shown that SW100 oysters exhibited a higher mortality when compared to SW0 and the remaining feeds, being unable to meet the demands for maintenance—a lower standard metabolic rate was measured in the SW100 oysters than in SW0 oysters (Ozório et al, ). Hence, a more satisfactory explanatory hypothesis would be differences in the growth rates between the various SW groups.…”
Section: Resultsmentioning
confidence: 75%
“…This is in accordance with the periods of allocation of energy to reserves followed by gonad development reported for several mollusks as a conservative strategy (Barber and Blake, ; Strohmeier et al, ). In a previous study, Rato et al () showed that oysters fed 100% macroalgae did not spawn, while the best reproductive success was observed in oysters fed with 25% macroalgae +75% microalgae and 100% microalgae diet (Rato et al, ). Due to EPA and DHA association with gametogenesis, an accumulation of these should have occurred prior to spawning.…”
Section: Discussionmentioning
confidence: 98%
“…This way and according to Rato et al (2018), when oysters are conditioned with a suitable diet, sufficient to meet nutritional requirements, such as 25% SW + 75% Alg and 100% Alg, the reserves of EPA and DHA are channeled to gametogenesis, leading to a higher percentage of viable (free-living) veliger larvae. In the case of 100% SW oysters, it seems that they mimic the behavior of C. gigas starved larvae, which selectively retained DHA during starvation, because they play other structural roles (da Costa et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, there is a growing trend to substitute live algae with more convenient, massproduced off-the-shelf feeds including dried algae, concentrated algal pastes, formulated feeds (including microencapsulated feeds), bacteria, and yeasts [23][24][25][26][27]. Reported disadvantages of substitute hatchery feeds have included settling, aggregation, bacterial degradation, leaching of nutrients, low digestibility of the cell wall material, cell settling, and disintegration for dried algae [23,27].…”
Section: Glossarymentioning
confidence: 99%